Ultrasound guided bilateral erector spinae plane block for post-surgical pain in patients after thoracic surgery (Medicina bolu, 2019)
Objective: To examine the analgesic efficacy of bilateral erector spinae plane (ESP) block compared with conventional treatment for pain after thoracic surgery.Methods: 34 patients with thoracic trauma were divided into 2 groups. Patients in group 1 (ESP block group, n = 14) received ultrasound-guided bilateral ESP block with 3 mg/kg of 0.375 % ropivacaine before anesthesia induction at the T6 transverse process level (Fig. 1). Patients in group 2 (acetaminophen and morphin group, n = 20) received acetaminophen (15 mg/kg every 6 hours – maximum 1 g) and morphine (10 mg every 8 hours) intravenously in the postoperative period. The primary study outcome was to evaluate pain at rest using a 10-point numeric rating scale (NRS). Mann – Whitney U-test was used for comparing NRS scores.Results: The postoperative pain level after extubating and duration of analgesia during which NRS was < 4 of 10 was compared be-tween the groups. The median pain score at rest after extubating in group 1 was 0 of 10 until hour 6, 3 of 10 at hour 8, and 4 of 10 at hours 10 and 12 postextubation. These were significantly less in comparison with group 2 (p = 0.0001). Patients in group 1 had a significantly higher mean duration of analgesia (11.04 ± 0.18 hours), during which NRS was < 4 of 10, compared with group 2 (4.18 ± 0.14 hours) (p = 0.0001). Conclusion: ESP block safely provided significantly better pain relief at rest for longer duration as compared to intravenous acetaminophen and morphine.